Understanding and Planning for Organized Community Sport in Public Parks: A Case Study of Policy and Practice in Perth - Middle, I.; Hedgcock, Dave; Jones, R.; Tye, M. (Routledge, 2017)
© 2017 Editorial Board, Urban Policy and ResearchEmerging shortages of community sporting facilities in Australian cities have led to calls for increased provision of playing fields through public park and open space planning processes. Drawing on a broad literature review and a specific case study of metropolitan Perth, this paper evaluates the value of organised sport as a function of contemporary public parks before proposing policy and practice to ensure that such an increase complements broader urban planning agendas. An analysis of the evolution of public park planning shows that, while the provision of organised sport was the primary function of public parks in the middle of the twentieth century, contemporary park planning is characterised by the embrace of broader ecological planning concepts such as green infrastructure and ecosystem services. These broader concepts are then applied to understand the value of organised sport held within public parks, including its unique benefits and notable limitations when considered alongside other forms of outdoor recreation. With these limitations in mind, this paper concludes by identifying existing and future policy and practice that can help to ensure that demand for community sporting facilities in new residential areas can be met in a manner that complements this ecological role for local parks.